Entrepreneurial Orientation Towards Competitive Advantage and Performance OF MSME - Alfazrin Nst; Zulkifli Musannip Efendi Siregar; Pitriyani Pitriyani (Agregat: Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine the effect of entrepreneurial orientation on the competitive advantage and performance of MSME. This research was conducted on a clothing retail store owner in Ajamu, Panai Hulu Subdistrict, Labuhanbatu Regency. The sample population used was 130 respondents using non-probability methods in the form of incidental and purposive sampling. This study, using the normality test and path analysis techniques with the help of the Amos software application. The results of the study found that Entrepreneurial Orientation has a positive and significant effect on Competitive Advantage. Entrepreneurial orientation has a positive and significant impact on the performance of MSME. Competitive Advantage has a positive and significant effect on the performance of MSME.